KELOLA JURNAL BARU: INSPIRASI DAN INISIASI PUBLIKASI ILMIAH PADA STKIP HUNIMUA SEBUAH PERGURUAN TINGGI KEPULAUAN - Riupassa, Pieter Agusthinus; Rumalolas, Risal; Luhulima, Yusran Baginda; Kelerey, Boysilan; Luhulima, Nurbai Saparwati; Tomia, Asmianti; Rumeon, Analia; Kelian, Emiyati; Nugraha, Irfan; Limba, Anatasija; Elim, Hendry Izaac (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
Higher education institutions in archipelagic regions face persistent challenges in scientific journal governance, limiting the visibility of lecturers’ scholarly contributions and constraining institutional publication capacity. STKIP Hunimua, located in the Maluku archipelagic region of Indonesia, experiences similar constraints, particularly in the absence of systematically and sustainably managed internal journal platforms. This community service initiative was conducted under the “Teaching Assistance 2025” Program of Pattimura University at STKIP Hunimua, East Seram Regency, Maluku Province. The program aimed to initiate and strengthen scientific journal development through structured academic mentoring. A participatory assistance approach was employed, actively engaging partner lecturers in scientific writing workshops, journal governance training, strategic planning discussions, and the facilitation of a journal management team. The program resulted in the establishment of two scholarly journals – HUNIMUA: Jurnal Pendidikan Kepulauan and UKARBATI: Jurnal Pengabdian Kepulauan – along with the development of an Open Journal System (OJS)-based platform (https://journal.stkiphunimua.ac.id). Additionally, lecturers demonstrated increased literacy and engagement in scholarly publishing practices. Beyond producing tangible outputs in the form of online journals, the initiative fostered a more proactive academic culture and strengthened institutional commitment to sustainable journal management. This program contributes to enhancing the academic capacity of higher education institutions in remote island contexts and demonstrates that collaborative, structured interventions can effectively establish viable scientific publication platforms, thereby supporting equitable participation in the digital transformative era in alignment with the vision of “Impactful Campus – Advanced Indonesia”.